Purification and characterization of the SegA protein of bacteriophage T4, an endonuclease related to proteins encoded by group I introns. - Sharma, M (1994)
Although not encoded by an intron, the bacteriophage T4 SegA protein shares common amino acid motifs with a family of proteins found within mobile group I introns present in fungi and phage. Each of these intron-encoded proteins is thought to initiate the homing of its own intron by cleaving the intronless DNA at or near the site of insertion. Previously, we have found that SegA also cleaves DNA. In this report, we have purified the SegA protein and characterized this endonuclease activity extensively. SegA protein cleaved circular and linear plasmids, DNA containing unmodified cytosines, and wild-type T4 DNA containing hydroxymethylated, glucosylated cytosines. In all cases, certain sites on the DNA were highly preferred for cleavage, but with increasing protein concentration or time of incubation, cleavage occurred at many sites. SegA cleaving activity was stimulated by the presence of ATP or ATP gamma S. Sequence analysis of three highly preferred cleavage sites did not reveal a simple consensus sequence, suggesting that even among highly preferred sites, SegA tolerates many different sequences. A T4 segA amber mutant that we constructed had no phenotype, and PCR analyses indicated that several T-even-related phages lack the segA gene. Taken together, our results show that SegA is an endonuclease with a hierarchy of site specificity, and these results are consistent with the insertion of segA DNA into the T4 genome some time after the divergence of the closely consistent with the insertion of segA DNA into the T4 genome some time after the divergence of the closely related T-even phages.